PEMODELAN ALIRAN LAHAR GUNUNG API MERAPI UNTUK PERHITUNGAN RISIKO KERUGIAN PADA PENGGUNAAN LAHAN TERDAMPAK DI BANTARAN SUNGAI BOYONG, PAKEM, SLEMAN, D.I. YOGYAKARTA - Kurniawan, Verry Octa; Mei, Estuning Tyas Wulan; Hadmoko, Danang Sri (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2019)
This study aims to conduct lahar of Mount Merapi on the Boyong River modeling. In addition, this study also to identificate the affected land use of the model, and analyze the risk of loss which are the focus of this study. Lahar modeling was made by using the LAHARZ application from DEMNAS 2018 data and 3 lahar volume scenarios based on the eruption of Mount Merapi in 1994. Identification of affected land use was carried out by using Sentinel-2B 2018 image interpretation with Maximum Likelihood Area (MLA) method, continued by verification using purposive sampling method in the field. Loss risk analysis was done by determining land use that has an economic value, which followed by classifying the level of damage based on the hazard level of lahar. The results of this study showed the effect of volcanic lahar volume and slope of Mount Merapi on surrounding land use. The generalization process in the DEM data did not have a significant difference to the lahar model. River morphology is very influential in this modeling output. Citra Sentinel-2B is suitable for identifying existing land use with the scale used is 1:10.000. The use of affected land was classified into 6 and 3 of which have economic values, namely settlements, buildings, and rice fields. There are 16 hamlets that are affected by the danger of lahar with residential land use which has the greatest total loss, while the use of wetland areas is the most extensive area of this danger.